2016
DOI: 10.1021/acs.jpcc.6b03313
|View full text |Cite
|
Sign up to set email alerts
|

Single Nanoparticle Plasmonic Spectroscopy for Study of Charge-Dependent Efflux Function of Multidrug ABC Transporters of Single Live Bacillus subtilis Cells

Abstract: Multidrug membrane transporters can selectively extrude a wide variety of structurally and functionally unrelated substrates, and they are responsible for ineffective treatment of a wide range of diseases (e.g., infection and cancer). Their underlying molecular mechanisms remain elusive. In this study, we functionalized Ag NPs (11 nm in diameter) with two biocompatible peptides (CALNNK, CALNNE) to prepare positively and negatively charged Ag-peptide NPs (Ag-CALNNK NPs+ζ, Ag-CALNNE NPs−4ζ), respectively. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…26,32,56 The biocompatibility of the functionalized Ag NPs (AgMUNH 2 NPs) could be attributed to the surface protecting layer of MUNH 2 and the low concentration of AgMUNH 2 NPs, as we reported previously. 33,40,57 At a low concentration, Ag NPs and functionalized Ag NPs do not inhibit bacterial growth and can be used to study the efflux function of single live bacterial cells. [29][30][31][32]58,59 Further, our previous studies also show that the positively charged peptide functionalized Ag NPs are more biocompatible with the zebrash embryonic development than negatively charged peptide functionalized Ag NPs.…”
Section: Size and Dose Dependent Inhibitory Effects Of Antibiotic Nanmentioning
confidence: 99%
See 1 more Smart Citation
“…26,32,56 The biocompatibility of the functionalized Ag NPs (AgMUNH 2 NPs) could be attributed to the surface protecting layer of MUNH 2 and the low concentration of AgMUNH 2 NPs, as we reported previously. 33,40,57 At a low concentration, Ag NPs and functionalized Ag NPs do not inhibit bacterial growth and can be used to study the efflux function of single live bacterial cells. [29][30][31][32]58,59 Further, our previous studies also show that the positively charged peptide functionalized Ag NPs are more biocompatible with the zebrash embryonic development than negatively charged peptide functionalized Ag NPs.…”
Section: Size and Dose Dependent Inhibitory Effects Of Antibiotic Nanmentioning
confidence: 99%
“…We have demonstrated that we can image and characterize the sizes of single Ag NPs at nanometer (nm) resolution in single live cells in situ in real time using size-dependent localized surface plasmon resonance (LSPR) spectra of single Ag NPs by dark-eld optical microscopy and spectroscopy (DFOMS). [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] We have used the size-dependent LSPR spectra of single Ag NPs to track the transport of single NPs in and out of single live cells and to determine the pore sizes of membrane transporters. 29,30 In our previous studies, we found dose and size dependent inhibitory effects of antibiotic nanocarriers (AgMUNH-Ox NPs) against Pseudomonas aeruginosa (Gram-negative bacterium) and Bacillus subtilis (Gram-positive bacterium).…”
Section: Introductionmentioning
confidence: 99%
“…No labelling with fluorophores is needed compared to fluorescence microscopy, which is perhaps the most employed technique for cellular imaging. Processes as diverse as the transport of single silver nanoparticles in zebrafish embryos [284], formation of lipid bilayers during exo- or endocytosis events [285], imaging and characterisation of single receptor molecules [286], transport kinetics in membrane [287] have been studied by LSPR monitoring of plasmonic nanoparticles. Intracellular p53 protein dynamics in HeLa cells was studied using a nanoscale surface plasmon-polariton fibre-tip-probe [288].…”
Section: Nanoplasmonicsmentioning
confidence: 99%
“…Localized surface plasmon resonance (LSPR) spectra of single NPs highly depend upon their sizes, shapes, dielectric constants, and surrounding environments, 2230 which enables us to use size-dependent LSPR spectra of single NPs to quantitatively determine sizes of single NPs in solution, in single live cells and embryos in situ in real time. 26, 3043…”
Section: Introductionmentioning
confidence: 99%
“…subtilis cells (Gram-positive bacterium). 31, 42, 43 Currently, 78 ABC transporters have been identified in B. subtilis , 4446 making B. subtilis a widely used model organism to study efflux function of ABC membrane transporters. We have also used size-dependent LSPR spectra of single Ag NPs to study transport dynamics of single MexAB-OprM membrane transporters in single live Pseudomonas aeruginosa cells (Gram negative bacterium).…”
Section: Introductionmentioning
confidence: 99%